Reshaping Translation Approaches to Unideal Texts: Translators’ Emotional Orientation towards Text User - Zheng, Jie; Xiong, Lingsong; Luo, Ruifeng (International Journal of Membrane Science and Technology, 2023)
In current translation practice, many source texts are hardly free of flaws, making them unable to realize their intended communicative effects, thus being regarded as “unideal texts”. Previous studies have probed into the translation approaches to unideal texts at the literal level, but unideal texts at the non-literal level are rarely explored. For such unideal texts, two translation approaches are available, namely faithful translation and rewriting. However, translation practitioners often adopt a continuum ranging from extremely faithful to entirely unfaithful approaches in translating unideal texts. Andre Lefevere presents three influential factors in his rewriting theory, namely patronage, ideology, and poetics, but his rewriting theory fails to explain the phenomenon of translation concerning rewriting unideal texts for other factors. This paper aims to investigate the influence of emotional orientation on translation approaches to unideal texts by comparing two English translation versions (a faithful translation and a rewritten version by two translators who have different emotional orientations towards the text user) of a Chinese speech transcript. Research methodologies include translation literature analysis, case studies, and an interview with the translator adopting rewriting as the approach. This paper finds that the influential factors in rewriting should include the emotional orientation of translators towards the text user.